Pakistan : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
This Selected Issues paper analyzes Pakistan's tax reform and revenue performance. The paper assesses the nature and magnitude of Pakistan's actual twin debt problem in a historical context, and reviews the policy options. The study highlights the factors explaining the recent stagnation in merchandise exports, and analyzes the country's export performance with regard to the linkages between performance and the structure of exports. The paper reviews a survey of poverty in Pakistan, and also provides a statistical appendix report of the country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet